Common Buckwheat-based EST Primers in the Genome of other Species of Fagopyrum (Nepal Agriculture Research Journal, 2009)
If the EST primers designed for one species can be used in related species, then the cost involvedin developing markers for DNA fingerprinting, genetic relationship studies, mapping, etc. forother species is significantly reduced. We tested the applicability of 17 EST primers developedfrom common buckwheat in other wild and cultivated Fagopyrum species. A total of 18accessions consisting of 4 subspecies and 2 species were used. Sequences of 93 cDNA cloneswere used to design primers using Primer3. Amplification products were different in bandintensity. In most of the cases, the bands of F. homotropicum were with high intensity. Allprimers showed single band except in Accession C9022. Three primers 23, 31 and 69 producedvery clear singe band. All primers amplified the genomic DNA of F. homotropicum (2x). Eightprimers amplified the DNA of all accessions. Results indicated that the transferability of ESTmarkers developed for common buckwheat decreased with an increase in genetic distancebetween them.Key words: Common buckwheat; EST markers; Fagopyrum species; transferabilityDOI: 10.3126/narj.v7i0.1863Nepal Agriculture Research Journal Vol.7 2006 pp.27-36